Redesigning Taman Hutan Kota PLN Medan (City Park) According to People’s Preferences - Rani Aurora Barus; Siti Nurkholila Hafni; Dwiki Alfajar Andrea (Talenta Publisher, 2020)
Taman Hutan Kota PLN Medan is one of important part from the city, if the park managed properly it would give a good impact to increase the quality of public space which is lead to make a positive and better contribution to people's lives who lived in the busy city like Medan. However, in reality, Taman Hutan Kota PLN cannot make a good performance as its function as public space and urban forest. To increase the level of people's happiness and develop urban quality at Medan, it is necessary to redesign Taman Hutan Kota PLN. The redesign’s purpose is to fulfill the people’s needs and hopes to this park and make better, satisfying, and responsive facilities to the user. Redesigning Taman Hutan Kota PLN will be based on people's preferences, perceptions, and perspectives. The preference, people's opinions, and documentation on the field will help us to discover what is the real reality and important resource for redesigning process so that the final result of the new Taman Hutan Kota PLN design can be a better park not only as public space and open green space but also as an alternative recreation facility for people in Medan.